Metaphorization of Palestine in political rhetoric: Interpreting types and functions of isti‘ārah in Abdel Fattah El-Sisi's speeches - Istiqomah Nur Aqilah; Andi Agussalim; Haeruddin; Zuhriah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Despite numerous studies have been conducted on contemporary Arab political speeches, the application of isti'ārah as an analytical category, particularly in discourse addressing the Palestinian issue, remains underexplored. Furthermore, prior work drawing on Arabic balāghah theory has concentrated predominantly on religious texts, poetry, and literary works, leaving the official speeches of Arab leaders largely unexamined. This study addresses that gap by identifying the types and structures of isti'ārah and examining the rhetorical and ideological representations they construct across five official Arabic speeches delivered by Abdel Fattah el-Sisi on Palestine. A qualitative textual analysis grounded in Arabic balāghah was employed. Non-literal expressions were identified and classified as either isti'ārah taṣrīḥiyyah or isti'ārah makniyyah through the identification of musta'ār lahu, musta'ār minhu, qarīnah, and al-jāmi', and subsequently mapped into representational patterns. Fourteen isti'ārah expressions were identified: five instances of isti'ārah taṣrīḥiyyah (35.71%) and nine of isti'ārah makniyyah (64.29%), indicating a predominance of implicit comparison. Four interrelated representational patterns emerged: Palestine as a suffering yet morally central issue; conflict as destructive and dehumanizing violence; morality as historical judgment and lost values; and political resolution as restoration, reconciliation, and reconstruction. Theoretically, the findings demonstrate that isti'ārah operates not as mere rhetorical ornamentation but as a structured linguistic strategy that concretizes political realities, intensifies moral evaluation, and legitimizes diplomatic solutions. Practically, the findings affirm the analytical relevance of classical balāghah to the study of contemporary Arab political discourse.